Economic analysis of shortfin scads fish (Decapterus spp) business using purse seine in Bone Regency, Indonesia. Issue 1 (October 2021) - Baso, Aris; Najamuddin; Firman; Chasyim Hasani, M.; Kasri
Abstract: Shortfin scads fish is a fish that has high economic value. The fishing business is an economic activity that is influenced by production factors to make a profit. The production factors referred to in this study are capital and expenditure costs. A purse seine is a fishing tool that contributes significantly to the fisheries economy in Bone Regency. The purpose of this study, among others, is to determine the level of income from the purse seine fishing gear business, calculate investment capital, expenses and profits, to analyse the financial aspects of the purse seine fishing gear business in Bone Regency. This research was conducted in June-September 2020. The location of this research was Bone Regency, South Sulawesi Province, Indonesia. The method used in this research is descriptive qualitative and quantitative methods with a purposive sampling method. The data analysis method uses business analysis using several indicators including income, R/C ratio, payback period, break-even point. The results showed that the average income level of fishing using purse seine was IDR 882, 860, 424 per year and it showed that the fishing gear business was feasible to run because the R / C ratio of the business was> 1 (2.17) payback period 1.01 years (12 months), and break-even point of production and price respectively 40, 130 kg/year and IDR 15, 293.